PRODUCTION AND MARKETING MIX OF GLUTINOUS CORN PRODUCTS IN UPT. AGRIBUSINESS DEVELOPMENT - Cahyasusanti, Ayu; Hendrarini, Hamidah; Sari Tondang, Ika (MediaTrend, 2025)
Increasing the production of products needed by customers and the marketing mix is the foundation in a product marketing to disseminate products and be increasingly recognized by the public. This study aims to examine the production and marketing of glutinous corn at UPT Agribusiness Development. This research was conducted in November 2023 at UPT Agribusiness Development. The research method applied is the trend analysis method approach and descriptive qualitative with data collection methods through observation, interviews, and documentation. The results showed that the development trend of glutinous corn production in UPT Agribusiness Development tends to fluctuate from 2020-2023, the marketing mix strategy implemented by UPT Agribusiness development uses the 7P method, namely there are innovative products, appropriate prices, strategic places, creative and targeted promotions, quality of people / HR, processes, and complete physical evidence. It can be concluded that the application of the right marketing mix strategy can increase the production and sales volume of sticky corn products.